Professional Position of Teacher-Psychologist in Terms of Optimizing the Education - A. D. Andreyeva (Научный диалог)
The problem of demand for teacher-psychologist by system of modern education is considered. The relevance of the study is determined by significant changes in the status and functions of psychologist in education, breaking the stereotype existing about his / her professional activities. The loss of the ideological essence of the profession of a school psychologist is also mentioned, its focus on the interests of the child, development of child’s personality. Organizational and conceptual aspects of the school relating to the reform of Russian education and enshrining in the new law on education are analysed. The transfer of the work of psychologist from educational institutions into centres of psycho-pedagogical, medical and social support significantly limits vocational field of psychologist. The high level of heterogeneity of pupils in the parameters of willingness to learn, neuropsychological status, social and cultural development is shown. The author argues that this situation calls for continuous psycho-pedagogical support of the educational process. The attitude of students’ parents to the professional position of the psychologist as a representative of the education system is discussed. Domination of the low level of trust in such professionals is revealed. The contradiction between the objective necessity of the presence of the school psychologist and the requirements of the new law on education is shown. The proneness to conflict of professional position of psychologist working in the education system is examined. The author indicates that the professional position of the psychologist in the conditions of optimizing the education loses the humanistic sense initially built in it.